Cover Picture: Emerging strategies of activatable MR imaging probes and their advantages for biomedical applications (View 5/2021). Issue 5 (27th October 2021) - Jin, Xiao; Yang, Weitao; Xu, Yan; Bian, Kexin; Zhang, Bingbo
Abstract : The use of contrast agents (CAs) can enhance the accuracy and specificity of MR imaging to disease diagnosis, but their imaging signals are "always‐on" regardless of whether they interact with target tissues or cells. In article number 20200141, Bingbo Zhang, Xiao Jin, Weitao Yang and their co‐workers summarize recent progress on the design strategies and principles of activatable CAs, and analyze their advantages in biomedical applications compared to conventional MR CAs, to improve target‐to‐background signal ratio for better diagnosis.